2022
DOI: 10.22382/wfs-2022-10
|View full text |Cite
|
Sign up to set email alerts
|

MOE Distribution in Visually graded Ponderosa Pine Lumber Harvested from Restoration Programs in Southern Oregon and Northern California

Abstract: Every year, restoration programs in Southern Oregon and Northern California produce large amounts of low-value ponderosa pine, Pinus ponderosa (PP) lumber. This material has a limited market in the United States. Engineered wood products, such as cross-laminated timber (CLT) and glulam, are expected to provide a value-added market to offset the high costs of restoration programs. However, restoration program lumber has larger amounts of juvenile wood and visual grades are reported to show lower mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…However, defining such pooled grade for lumber generated from small logs harvested in restoration projects would require the determination of the statistical distribution of MOE in larger samples derived from a representative number of stands and One potential reason for the low-shear capacity may be the presence of interlaminar gaps detected in 80% of the specimens. These gaps led to delamination failures in standard bond integrity tests observed in a parallel study conducted within this project (Jahedi et al 2023). The interlaminar gaps may have resulted from a combination of high thickness variations along the laminations and uneven clamping pressure.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, defining such pooled grade for lumber generated from small logs harvested in restoration projects would require the determination of the statistical distribution of MOE in larger samples derived from a representative number of stands and One potential reason for the low-shear capacity may be the presence of interlaminar gaps detected in 80% of the specimens. These gaps led to delamination failures in standard bond integrity tests observed in a parallel study conducted within this project (Jahedi et al 2023). The interlaminar gaps may have resulted from a combination of high thickness variations along the laminations and uneven clamping pressure.…”
Section: Discussionmentioning
confidence: 88%
“…On average, interlaminar gaps covered 0.9% of the bond line perimeter of LP and 1.8% of the IP bending specimens. Bond integrity test samples are reported separately and showed that these gaps were the main cause for poor resistance to delamination (Jahedi et al 2023). In addition, that study isolated the impact of adhesive/species compatibilities and demonstrated that interlaminar gaps were caused by fabrication issues, which could include excessive thickness variations within laminations, uneven clamping pressure, or a combination of both.…”
Section: Fabrication Of Prototype Pp Cltmentioning
confidence: 98%
See 1 more Smart Citation
“…White fir, for example, is a low-value species that only has preliminary structural data, but could potentially be used in a similar application to Ponderosa pine in CLT. There are several recently completed and planned low-value species testing projects undertaken at the TallWood Design Institute and Oregon State University on Oregon-harvested Ponderosa pine in collaboration with Vaagen Timbers, and, additionally, California white fir and Alaskan spruce using a more capital-intensive process with a large timber press; there is growing interest in the structural and commercial possibilities for these materials, along with the increasing local, less-capital intensive efforts as noted above [10][11][12]. Furthermore, continued development of construction details and the application of these panels to other building types, such as housing and multi-story structures, is a potential area of study.…”
Section: Discussionmentioning
confidence: 99%